Socialization of Basketball Game Rules - I Putu Agus Dharma Hita; Komang Ayu Krisna Dewi; I Ketut Addy Putra Indrawan; Elsa Ariestika; Doni Pranata (Peneliti Teknologi Teknik Indonesia, 2023)
The community service activity entitled